The relationship between perceived family support, pain comprehension, catastrophizing and pain intensity among chronic pain patients in Selayang Hospital - Nur Aini A. Suner (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The present research examined the relationship between perception, (i.e. perceived family support) components of cognition, (i.e. comprehension and catastrophizing) and pain intensity experienced by chronic pain patients. It was hypothesized that (a) the more support perceived the lesser pain and (b) the better comprehension on pain the lesser pain. Catastrophizing was hypothesized to moderate the relationship between perceived family support, pain comprehension and pain intensity. The study utilized the correlational design. The sample consisted of sixty chronic pain outpatients from Selayang Hospital, with a variety of pain condition i.e. low back pain, neck pain, and shoulder pain. Ten of these sixty patients were selected to undergo a one-to-one interview session, in order to provide qualitative information. Instruments used in this research were Medical Outcomes Study-Social Support Survey (MOS-SS); Patient Pain Questionnaire (P.P.Q.); Pain Catastrophizing Scale (PCS); and Short Form McGill Pain Questionnaire (SF-MPQ). The results of the study indicated that perceived family support was not related to pain intensity. However, pain comprehension was positively related to the experience of pain. Catastrophizing neither increased nor decreased the relationship between perceived family support, pain comprehension and pain intensity. Qualitative analysis revealed that perceived family support, pain comprehension and catastrophizing influenced patients' illness belief and pain perception. The findings of this study have some implications in the approach used in pain clinics as well as the design of pain management intervention programs in Malaysia.